Kontribusi KH. Abdul Latif dalam Mengembangkan Madrasah dan Pondok Pesantren di Banten - Rohbiyah Rohbiyah; Wasehudin Wasehudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia's oldest institutions were its Islamic boarding schools. However, the most pressing issue is how pesantren instill moral principles, which serve as the incubators of a society's intellectual capacities and noble character (al-akhlaq al-karimah). where the author was interested in researching one of the pioneers of Islamic boarding schools in Banten, Indonesia. It was not an exaggeration to repeat KH. Abdul Latif's life story and thoughts on education. Researchers hope readers may follow his struggle to further development in the fields of education and society, as researchers want to examine one of the Islamic boarding schools in Banten which he founded. particular in the Banten region. Sadly, we can all agree that his kind of spirit was becoming increasingly rare in today's world. Because of this, we must reignite his fervent passion and unwavering dedication to advancing Islamic religious education.